Graphene and related 2D materials: An overview of the Raman studies. (28th December 2017) - Paillet, Matthieu; Parret, Romain; Sauvajol, Jean‐Louis; Colomban, Philippe
Abstract : After a brief overview of the discovery and the Raman study of new forms of carbons (intercalated graphite, carbon fiber, fullerenes, carbon nanotubes), the invaluable contribution of late Professor M. Dresselhaus is noted, and the 10 reviews and 9 contributions collected to present a picture of the current Raman investigations of graphene and related 2D materials (such as black phosphorus, MoS2 ) are introduced. Methods for numbering the graphene layers, the effects of external perturbations (temperature, pressure, doping, and magnetic field) on the phonons of graphene, characterization of the chemical and structural properties of graphene at the nanoscale level by tip‐enhanced Raman spectroscopy, surface enhanced Raman spectroscopy and hyperspectral imaging, and applications combining graphene and Raman spectroscopy are addressed. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : After a brief overview of the discovery and the Raman study of new forms of carbons such as intercalated graphites, carbon fiber, fullerenes, nanotubes, the invaluable contribution of late Professor M. Dresselhaus is noted, and the 10 reviews and 10 contributions collected to present a picture of the present Raman investigations of graphene and related 2D materials such as black phosphorus, MoS2, are presented.